De mères à Grande Mère - Giulia Pedrucci (Cahiers Mondes Anciens)
Sicily has an impressive number of terracottas representing women with children, between them we find a very rare motif in the ancient world (above all in continental Greece) : the breast-feeding woman. In the effort to explain this extraordinary archaeological documentation, it is necessary to review the very powerful « myths » of the « Sicilian Great Mother » and of Sicily as a land completely sacred to Demeter and Kore. The origins of the cults connected with the terrecottas of women with children have to be searched for, in our opinion, in the ante-hellenic cultures, taking onto account the possibility of direct contacts with the ancient Near East.